El esclavo imaginado hoy en las artes visuales en el oriente de Cuba - María Elena Orozco Melgar; Etna Cecilia Sanz Pérez (Études Caribéennes)
The present work explores the image of the «negro» in the visual arts of East Cuba. It examines the forms in which the colonial engraves and paintings approached the racialized individual as a subject of representation. Then, the text analyzes the «ways of seen» to the negro as an expression of the close relationship between race and nation typical of the Cuban culture during the 20th century. Such theme assumes peculiar features in the artistic ambience of the East of the island. Finally, it inquiries about a series of topics (Africa, slavery, cimarronaje, rebelliousness, virility), as they are re-interpreted by artists preforming in contemporaneity.